Impact of Brief Lactation Rotation in Residency on Decision to Refer for Lactation Support - Megan M. Kindred; Kelsie R. Barta (Journal of Primary Care & Community Health)
Introduction: Breastfeeding challenges may be difficult to address within the constraints of a typical well-child visit. A team-based approach, including lactation consultants, can reduce physician workload, increase breastfeeding self-efficacy, and increase patient satisfaction. Continuity of care issues, including absent or delayed referrals, hinder patient access to skilled lactation support. Objectives: To examine the post-residency referral patterns of physicians to lactation consultants among physicians who did or did not participate in a brief outpatient lactation rotation at an academic lactation clinic during residency. Methods: A cross-sectional online survey of physicians who completed residency programs in pediatrics, family medicine, or medicine-pediatrics between 2013 and 2022 was conducted using REDCap; 46 valid responses were received. Results: Respondents who participated in a brief outpatient lactation rotation during residency refer patients to lactation consultants with significantly higher frequency than those who did not complete the rotation. Among those with lactation consultants in their geographic area, this relationship remained significant even when adjusting for residency type, gender, experience with an inpatient lactation consultant, and infant feeding attitudes using multiple linear regression. Conclusions: An outpatient lactation rotation during medical residency may increase the likelihood of referring to a lactation consultant in post-residency practice, which can improve breastfeeding outcomes.